REPRESENTASI INTERAKSI PUSTAKAWAN DAN PEMUSTAKA PENYANDANG BIPOLAR DALAM FILM KUKIRA KAU RUMAH (ANALISIS SEMIOTIKA ROLAND BARTHES) - Alya Ratu Balqis Ari; Anang Anas Azhar (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Film is the result of a process of cultural depiction and a tool of artistic expression. Film as one of the reforms or can be interpreted as a mass communication tool consists of a combination of various technologies formed into one. The movie that has come to the author's attention for this analytical research is a movie entitled I thought you were home. A family drama movie that raises the mental issues of a teenager with bipolar disease. Where in each scene has a moral message and one of them is when there is an interaction between the Librarian and the main character while in the library. The formulation of the problem that was the focus of the research was the meaning of the interaction between librarians and library users when conducting circulation services in the movie I thought you were home by Umay Shahab. The focus of the research is located in the scene duration 18.33 - 20.47. This study aimed to describe the interactions that occur between librarians in providing circulation services to visitors, here the researcher's assessment is related to the attitude of empathy, reliability, and attention of librarians. The research method used by researchers is descriptive qualitative with the semiotic analysis technique of roland barthes. The results obtained in this study, librarians are very professional in conducting interactions, and the value that becomes the benchmark of researchers meets the 3 criteria of a library user in accordance with the formulation of the problem in this study.